THE EFFECT OF SLIDESGO-ASSISTED QUANTUM TEACHING MODEL ON STUDENT ACTIVITY, MOTIVATION AND LEARNING OUTCOMES - Yuliana Hamzah; Muhammad Nawir; Hidayah Quraish (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
The aim of the study was to determine the effect of the Slidesgo-assisted Quantum Teaching learning model on motivational activities and social studies learning outcomes simultaneously in class V Region II Barru District. This type of research is quasi-experimental (Quasi-Experimental), with the Nonequivalent Control Group Design. The number of samples in this study were 23 people, consisting of 14 people from the experimental class and 9 people from the control class. Data collection methods used are learning achievement tests, questionnaires to measure learning activity and motivation, and documentation. Data analysis techniques used are descriptive statistical approaches and inferential analysis, and Manova hypothesis testing. The results obtained were the Slidesgo-assisted Quantum Teaching learning model on student activity, motivation and learning outcomes with a significant value of 0.000 0.05, which means that there was an influence of the Slidesgo-assisted Quantum Teaching model on the activity, motivation and learning outcomes of social studies class V students in Region II District. Barru District of Barru. So it can be concluded that the slidesgo quantum teaching learning model can affect the activity, motivation and social studies learning outcomes of class V students, Barru District, Barru Regency.